Gender Differences and Postoperative Delirium in Adult Patients Undergoing Cardiac Valve Surgery - Wang, Hongbai; Guo, Xiaoxiao; Zhu, Xianlin; Li, Yinan; Jia, Yuan; Zhang, Zhe; Yuan, Su; Yan, Fuxia (Frontiers in Cardiovascular Medicine, 2021)
Background: Postoperative delirium (POD) is common in patients following cardiac surgery. According to studies on non-cardiac surgery, males suffered from higher incidence of POD. However, there is no report about effect of gender differences on POD occurrence in cardiac surgery patients. The aim of this study was to investigate the effect of gender differences on POD occurrence in adult patients after cardiac valve surgery. Methods: This is a retrospective case-control study. We recorded the clinical data in adult patients who underwent elective cardiac valve surgery from May 2019 to October 2020. POD was assessed by the Confusion Assessment Method for Intensive Care Unit. Univariate analysis was used to screen the potential risk factors. Collinearity analysis was conducted to detect overlapping predictor variables on the outcomes. A multivariate logistic regression with odds ratio (OR) and 95% confidence interval (CI) was used to identify the independent risk factors. The Hosmer-Lemeshow test was performed to show the good calibration of the logistic regression model. Results: In total, we recorded the perioperative data in 431 adult patients, including 212 males and 219 females. Sixty patients suffered from POD, including 39 males and 21 females. Twenty-one perioperative variables were selected, and 11 were screened by univariate analysis. We did not detect the severe collinearity among the 11 variables. Male gender was identified as a significant risk factor in POD occurrence in patients undergoing cardiac surgery (Adjusted OR: 2.213, 95% CI: 1.049–4.670, P = 0.037). The Hosmer-Lemeshow test demonstrated good calibration of the logistic regression model (χ2 = 7.238, P = 0.511). Besides, compared with females, the relationship of male and delirium subtypes was as follows: (1) hyperactive: adjusted OR: 3.384, 95% CI: 1.335–8.580, P = 0.010; (2) hypoactive: adjusted OR: 0.509, 95% CI: 0.147–1.766, P = 0.287. A Stratification analysis by age demonstrated that the males showed higher POD incidence in patients aged younger than 60 years (adjusted OR: 4.384, 95% CI: 1.318–14.586, P = 0.016). Conclusions: Male gender is an important risk factor in POD occurrence in patients following cardiac surgery. Furthermore, the incidence of hyperactive delirium is higher in males. Besides, the male patients aged younger than 60 years are at high risk of POD. We should pay more attention to the male patients to prevent their POD occurrence.